No gender-related differences in the severity of nephropathia epidemica, Germany - Krautkrämer, Ellen; Grouls, Stephan; Urban, Eva Katharina; Schnitzler, Paul; Zeier, Martin (BMC infectious diseases, 2013)
The number of cases of hantavirus disease caused by Puumala virus is increasing enormously in Germany within the last years. Men are overrepresented in hantavirus disease and differences in course and symptoms in relation to gender were reported from several countries. This study was conducted to define possible gender-specific risk factors and aspects of severity in hantavirus infections occurring in Germany.
Gesehen am 28.10.2021